Institutional Barriers to Providing Oral Health Services for Underserved Populations in New York City - Chlix Ramos-Rodriguez, DMD; Mark D. Schwartz, MD; Vincent Rogers, DDS, MPH; Victor Alos, DDS (Blackwell Synergy, 2004)
We sought to explore institutional barriers to the provision of oral health services for the underserved among inner-city health centers.